Trauma Informed Care in the Perinatal Period Growing Forward. (Protecting children and young people series, 2015)
Studies of traumatic stress, attachment, and neurobiology, confirm the importance of the mother and child bond for life-long health. Yet intergenerational cycles of childhood maltreatment and psychiatric vulnerability may endanger that bond to warrant a prevention approach. Trauma-informed care and interventions in maternity services may be needed.